ORANG ASING SEBAGAI SUBJEK HAK ATAS TANAH DI INDONESIA - FX. Sumarja (Faculty of Law, Universitas Diponegoro, 2015)
This research aims at finding foreigners who may be the subject of Land Use Rights and Lease Rights for the building. The results of the study indicate: 1) Period, BAL-PP 41 of 1996, and the period of 2010 - now, foreigners who can be the subject of land rights are foreigners as the resident of Indonesia; 2) Period, PP 41 of 1996 - in 2010, foreigners who may be the subject of land rights was expanded into foreigners as both a resident of Indonesia and has a residence permit in Indonesia.